Umbilical cord sclerosis as an indicator of congenital syphilis. Issue 11 (November 1989) - Knowles, S; Frost, T
Abstract : In two cases of congenital syphilis examination of the umbilical cord showed a distinctive picture of perivascular sclerosis and inflammation. Large numbers of spirochaetes were shown in the sclerotic zone in both cases. No organisms were demonstrable in the placental disc and there were no morphological changes suggestive of syphilis. It is concluded that the finding of sclerosing funisitis, together with the clinical circumstances, should raise the possibility of congenital syphilis.